Generic and Shiga toxin-producing Escherichia coli (O157:H7) contamination of lettuce and radish microgreens grown in peat moss and perlite. (May 2020) - Işık, Hasan; Topalcengiz, Zeynal; Güner, Senem; Aksoy, Aziz
Abstract: Pathogens can be transferred to microgreens from seeds, irrigation water and growth media. The purpose of this study was to evaluate the contamination of Shiga toxin-producing Escherichia coli (STEC O157:H7) and generic E. coli to lettuce and radish microgreens grown in spray and bottom irrigated peat moss and perlite. Lettuce and radish seeds were grown in nalidixic acid resistant E. coli strains inoculated peat moss and perlite. Populations of cells were enumerated on edible and inedible part of plants. Survival of E. coli strains were also examined in growth media for 28 days. Type of irrigation did not affect the population of cells transferred to edible part of plants ( P  > 0.05). Populations of E. coli contaminating the inedible part of plant were higher in perlite than those in peat moss ( P  < 0.05). No E. coli O157:H7 was detected by enrichment in edible part of lettuce grown in peat moss. Radish microgreens had high generic E. coli and E. coli O157:H7 populations (4.15–6.49 log CFU/g) regardless of growing media. E. coli O157:H7 showed similar survival trends to generic E. coli in peat moss, perlite and plant growth solution over 28 days of storage. Cultivation of microgreens in perlite requires umbrella strategies to mitigate risk including irrigation water quality, seed decontamination and postharvest treatments to prevent contamination. Highlights: E. coli O157:H7 did not survive on edible part of lettuce microgreens grown in peat. E. coli population were up to 6.5 log CFU/g on edible part of radish microgreens. Type of irrigation did not affect E. coli populations on microgreens. Generic E. coli population was higher than E. coli O157:H7 on lettuce microgreens.